Related Party Transactions, Family Ownership, and Earnings Management in Indonesia - Subastian, Levina Ulfa; Widagdo, Ari Kuncara; Setiawan, Doddy (University of Merdeka Malang, 2021)
The purpose of earnings management practice is to reach the profit goals the company wants to achieve. Therefore, this study aims to determine the relationship between related party transactions and earnings management in Indonesia by balanced panel data from consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The number of samples used in this study was 102 firm-year observations. The results showed that related party transactions positively and significantly improved corporate earnings management, with discretionary accrual as a proxy. The presence of family ownership strengthens the relationship between related party transactions and earnings management. Also, it shows that the control variable: public accountant from BIG4, company size, company losses, and ROA affect accrual earnings management. The leverage does not affect accrual earnings management. The study result indicates that family business ownership encourages an entrenchment effect that is detrimental to the company. It is carried out through related party transactions then manipulated by using accrual earnings management practices.DOI: 10.26905/jkdp.v25i3.5778